Zwierzęta w gospodarce mieszkańców wczesnośredniowiecznego grodu w Dakowach Mokrych (stan. 1), powiat nowotomyski, woj. wielkopolskie - Mizerka-Urbaniak, Jagoda; Piątkowska-Małecka, Joanna (Slavia Antiqua. Rocznik poświęcony starożytnościom słowiańskim, 2025)
The article presents the results of an archaeo-zoological analysis of a post-consumption collection of 2,226 bone fragments, and a set of bone artefacts from an early medieval (second half of the 9th – first half of the 10th century) settlement in Dakowy Mokre. The inhabitants’ economy was based on the breeding of domesticated mammals and birds, supplemented to a small extent by hunting wild animals: deer, roe deer, wild boar and hares. In animal husbandry, the most important role was played by small cattle used as a source of meat and fat, as well as milk and draught power. Of lesser importance were medium-sized pigs, sheep, goats, and domestic chickens. These animals provided mainly food products (meat, fat, eggs). Animal products were also used, including bone raw material used to make various items (carding combs, spikes, needles).